(untitled) (The Pakistan Development Review, 1999)
Pakistan is a large country with a population estimated at 130.580 million.1 The economy has a low-income of US 490 per capita, with an estimated Purchasing Power Parity (PPP) of US 2230.2 It has managed to achieve substantial economic growth in the past thirty years until the dawn of 1990s. The growth rate has averaged 6.8 percent, 4.8 percent and 6.5 percent in 1960s, 70s and 80s, respectively.3 Evidence from the National Income Accounts, Household Surveys and time series data on the real wages of unskilled workers shows that economic growth has contributed to reduce consumption poverty4 in Pakistan. The table placed as Appendix A at the end shows that GDP per capita has increased in real terms by about 63 percent between 1972-73 and 1990-91. Private consumption per capita also increased in real terms by about 36 percent. Despite the fact that the population has nearly doubled during the period, there have been gains in income and consumption in per capita terms.